Escherichia coli e Salmonella sp. em suiformes nativos e exóticos assintomáticos em criações comerciais do estado de Goiás - Faria, Adriana Marques (2016)
The closeness beteween wild and domestic animals with humans may result in common diseases involving these three groups, including zoonotic and antropozoonotic diseases. The study of bacteria and disease that affects animals is an important way to approach epidemiologic control and sanitary vigilance, as we do not understand the roll of wild animals in transmitting diseases among wild, exotic and domestic animals. The main objective of the present study was to search the presence of Escherichia coli and Salmonella sp. from rectal swabs of non-domesticated Suiformes in Commercial herds in Goiás State. It was collected rectal swabs of 100 Sus scrofa scrofa, 60 T. pecari and 30 P. tajacu, from different ages. The samples were used in order to obtain the isolation, antimicrobial profile, hemolisin test for E. coli and virulence and resistance gene presences in both bacteria. The serotyping was performed with polyvalent anti-O serum and the virulence and resistance gene deteccion by PCR technique. The results shown high rates of antimicrobial resistance and virulence and resistance genes in analyzed groups of E. coli. The isolation of Salmonella sp. occurred in one sample of S. scrofa, with high rates of antimicrobial resistance also, but no resistance and virulence genes were detected in this isolate. We must pay attention to the possibility of horizontal gene transference of virulence factors and resistance trough contaminated water and food, that may transform commensal bacteria in possible pathogenic agents. It is conclude: that Salmonella sp. is not commonly isolated from T. pecari and P. tajacu, showing low frequency of isolation in S. scrofa in these conditions; and E. coli with multidrug resistance patterns is isolated from S. scrofa, T. pecari and P. tajacu in commercial herds from Goiás State.